Walden - Thoreau, Henry David, 1817-1862 (Thoreau, Henry David, 1817-1862. Works. 1971., 2016)
One of the most influential and compelling books in American literature, Walden is a vivid account of the years that Henry D. Thoreau spent alone in a secluded cabin at Walden Pond. This edition--introduced by noted American writer John Updike--celebrates the perennial importance of a classic work, originally published in 1854. Much of Walden's material is derived from Thoreau's journals and contains such engaging pieces from the lively "Where I Lived, and What I Lived For" and "Brute Neighbors" to the serene "Reading" and "The Pond in the Winter." Other famous sections involve Thoreau's visits with a Canadian woodcutter and with an Irish family, a trip to Concord, and a description of his bean field. This is the complete and authoritative text of Walden--as close to Thoreau's original intention as all available evidence allows. This is the authoritative text of Walden and the ideal presentation of Thoreau's great document of social criticism and dissent.